Adsorption of sulfamethazine by multi-walled carbon nanotubes: effects of aqueous solution chemistry1. Issue 32 (10th April 2015) - Yang, Quanquan; Chen, Guangcai; Zhang, Jianfeng; Li, Helian
<x xml:space="preserve">Abstract</x> The adsorption of SMZ by MWCNTs was studied under varied pH, ionic strength, cations and anions in solution. The results indicated that hydrophobic and electrostatic interactions were the main adsorption mechanisms, and π–π interaction also played an important role.